Turkey reframed : constituting neoliberal hegemony - Akça, İsmet; Bekmen, Ahmet; Özden, Barış Alp, 1978- (PlutoPress, 2014)
Turkey Reframed documents the first decade of the 2000s, a period of radical change in Turkish society and politics, which has been marked by the major economic crisis of 2001 and the coming to power of ex-Islamist cadres organised under the Justice and Development Party (AKP). The contributors analyse this period of radical change, with its continuities and breaks, and its main actor, the AKP, in relation to the creation of a neoliberal hegemony in post-1980 Turkey. They look at the conflictual, turbulent and painful history of neoliberal hegemony and the contested stabilisation strategy of the AKP government. Turkey Reframed is a cutting-edge guide for students, scholars and other interested readers who want to understand this period in Turkey's recent history and its social tensions.